Genetic Variation among African Swine Fever Genotype II Viruses, Eastern and Central Europe - Carmina Gallardo; Jovita Fernández-Pinero; Virginia Pelayo; Ismail Gazaev; Iwona Markowska-Daniel; Gediminas Pridotkas; Raquel Nieto; Paloma Fernández-Pacheco; Svetlana Bokhan; Oleg Nevolko; Zhanna Drozhzhe; Covadonga Pérez; et al. (Emerging Infectious Diseases, 2014)
African swine fever virus (ASFV) was first reported in eastern Europe/Eurasia in 2007. Continued spread of ASFV has placed central European countries at risk, and in 2014, ASFV was detected in Lithuania and Poland. Sequencing showed the isolates are identical to a 2013 ASFV from Belarus but differ from ASFV isolated in Georgia in 2007.